Antifungal activity of propolis against Candidaspecies isolated from cases of chronic periodontitis - Ana Beatriz Sotero SIQUEIRA; Larissa Rodrigues Nolasco de Araújo RODRIGUEZ; Ruth Karine Barroso SANTOS; Ricardo Romulo Batista MARINHO; Sheila ABREU; Raniel Fernandes PEIXOTO; Bruno César de Vasconcelos GURGEL (Sociedade Brasileira de Pesquisa Odontológica, 2015)
This research evaluated the fungistatic and fungicidal activities of red propolis alcoholic extract (RPAE) against different Candida species isolated from chronic periodontitis cases, and compared with chlorhexidine (CHX). Nineteen samples of Candida species (C. albicans [n = 12], C. tropicalis [n = 5] andC. glabrata[n = 2]) isolated from chronic periodontitis cases were analyzed. The fungistatic and fungicidal activity of both RPAE and CHX were evaluated using fluconazole and C. parapsilosis (ATCC 6258) as a control. Fungistatic activity was analyzed based on the Clinical and Laboratory Standards Institute (CLSI) reference procedure to determine the minimum inhibitory concentrations. Fungicidal activity was established according to the absence of fungal growth on Sabouraud Dextrose Agar medium. The fungistatic and fungicidal activities of RPAE were observed, respectively, at 32-64 μg/mL and 64-512 μg/mL for C.albicans, 64 μg/mL and 64-256 μg/mL for C. glabrata, and 32-64 μg/mL and 64 µg/mL for C. tropicalis. CHX fungistatic activity was observed at concentrations of 0.003-1.92 µg/mL for C. albicans, 1.92 µg/mL for C. glabrata, and 0.03-1.92 µg/mL for C. tropicalis. Fluconazole fungistatic activity ranged between 1-64 μg/mL, and fungicidal activity occurred at 8-64 μg/mL, for the threeCandida species analyzed. All the Candidaspecies were susceptible to RPAE antifungal activity, but five samples ofC.albicans, one ofC.tropicalis and one ofC.glabrata were resistant to fluconazole antifungal activity. CHX showed fungistatic activity against all the Candida species analyzed. The antifungal potential of these substances suggests that they can be applied as an alternative treatment for diseases affected by these species.